Subterranean Deuteraphorura Absolon, 1901, (Hexapoda, Collembola) of the Western Carpathians - Troglomorphy at the northern distributional limit in Europe. - Andrea Parimuchová; Martina Žurovcová; Vladimír Papáč; Ľubomír Kováč (PLoS ONE)
An integrative approach employing molecular, morphological and geographical data were applied to species delimitation among Deuteraphorura congeners occupying caves of the Western Carpathian Mts. A new species of Deuteraphorura from the Western Carpathians is described. D. muranensis sp. nov. belongs among species with 4 pso at the hind margin of the head and possesses highly troglomorphic features. It is conspicuous with its distinctly elongated claws and long, hair-like body chaetae. The status of the new species was confirmed by DNA barcoding based on the mitochondrial COI marker. Populations of D. kratochvili (Nosek, 1963), the most widespread species, were studied in detail. Both ABGD and PTP analyses brought results congruent with geography, i.e. the molecular and geographic distance of the populations were positively correlated. However, some molecular separation based on pairwise distance and the number of substitutions was indicated within two of the studied populations. Despite the indistinct morphological differences, the tested populations were well isolated both geographically and genetically, which indicates that each studied population may represent a cryptic species. The troglomorphy of cave Collembola at the northernmost border of the distribution of cave-adapted species in the Europe is discussed. It is clear that the level of troglomorphy is closely associated with conditions of the microhabitat occupied by the individual subterranean species. The results of our study enhance the importance of the Western Carpathians regarding the diversity pattern of obligate cave species in Europe.